Digital Watermarking Using Advanced Encryption Standard (AES) And Steganography Methods to Increase The Level Of Security Of User Data In The Image Files On Internet Network - Khoerul Umam (Informatika Universitas Siliwangi, 2020)
The spread of digital media on the internet was very broad, fast, and cannot be monitored in a structured manner about what media has been uploaded and distributed on the internet network. The spread of digital media like this was very difficult to detect whether the media that shared was privately owned or that of others that is re-shared by media theft or digital media piracy. One step to overcome the theft of digital works is to give them a watermark, which is an identity that is placed on top of the work. However, this is still considered unsafe because the identity attached can be cut and manipulated again until it is not visible. In addition, the use of Steganography method to hide messages in an image can still be manipulated by adding messages continuously so that it accumulates and damages the original owner of the image. In this article, the author provides a solution called Digital Watermarking, a step of encrypting the data of the original owner of the work and putting it into the image of his work. This watermark cannot be seen clearly, but actually in the media there is encrypted data with a strong Advanced Encryption Standard (AES) method. As a result, a tool that can improve the security of media owner data by combining the AES and Steganogaphy methods in the formation of new media that cannot be changed anymore. So, when the media is stolen and used by others and has been edited, the owner's personal data can never be changed.